2021
DOI: 10.1108/ijem-06-2020-0325
|View full text |Cite
|
Sign up to set email alerts
|

The role of culture in student discipline of secondary schools in cross-cultural context: a systematic literature review and future research agenda

Abstract: PurposeThe present study is a systematic review that identifies future research avenues on culture and discipline in secondary schools in a cross-cultural context.Design/methodology/approachThe literature, as published in top management, education and psychology journals, was reviewed around culture and discipline in secondary schools. This systematic literature review (SLR) used several preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and categorised the studies published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…A student with good self-discipline is likely to achieve more. The study outcomes supported previous research (Duckworth and Seligman 2005;Chamorro-Premuzic and Furnham 2008;Jayawardena 2021;Baumann et al 2020), indicating the role of self-discipline in academic results. Students with discipline perform better on all fronts and achieve success in life (Baumann et al 2020).…”
Section: Resultssupporting
confidence: 89%
“…A student with good self-discipline is likely to achieve more. The study outcomes supported previous research (Duckworth and Seligman 2005;Chamorro-Premuzic and Furnham 2008;Jayawardena 2021;Baumann et al 2020), indicating the role of self-discipline in academic results. Students with discipline perform better on all fronts and achieve success in life (Baumann et al 2020).…”
Section: Resultssupporting
confidence: 89%
“…The findings regarding the significance of cultural practices, such as Teacher-Elderly Guidance, align with existing literature that emphasises the crucial role of cultural practices in shaping discipline management. Studies by Jayawardena (2021) and Espelage et al (2022) similarly highlight the influence of cultural values and traditions on learner discipline, particularly the role of experienced teachers as cultural guardians. These findings underscore the significant role Onaolapo & Makhasane, 2024…”
Section: The Cultural Significance Of Teacher-elderly Guidance On Lea...mentioning
confidence: 99%
“…In Nigeria, elders are revered for their wisdom and experience, and their advice is sought in personal matters and educational contexts. Studies by Ezemba et al (2021) and Jayawardena (2021) underscore the profound influence of cultural values on educational practices in Nigeria, highlighting the unique role of elderly teachers in guiding younger learners. This cultural reliance on elderly guidance further extends to learner discipline, where the impartation of discipline often involves the sage counsel of respected teachers, fostering a holistic approach that considers cultural values.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were found to have been focussed on the use of storyline-based video games in classrooms (Casañ, 2017;Dincelli & Smith, 2020;Oztaysi, Dogan, & Gul, 2019) and on the visualization of folk dances linked to cultural heritages (Kico, Grammalidis, Christidis, & Liarokapis, 2018). Little research was found to have investigated sustainable tourism through gamification techniques and applications (Jayawardena, 2021;Negruşa, Toader, Sofică, Tutunea, & Rus, 2015), climate change communication through online games (Ouariachi, Olvera-Lobo, & Gutiérrez-Pérez, 2017), and gamification for clinical treatments (Richards & Caldwell, 2017).…”
Section: Cluster Identificationmentioning
confidence: 99%